2017
DOI: 10.1055/s-0043-102397
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of single-balloon enteroscopy in management of gastrointestinal bleeding in patients with a left ventricular assist device

Abstract: Background and study aims Left ventricular assist devices (LVADs) are currently the standard of care in treatment of patients with end-stage heart failure waiting for heart transplant as well as destination therapy for non-transplant candidates. However, patients with LVADs are at increased risk of gastrointestinal bleeding due to the device’s unique effects on hemodynamics. A major source of gastrointestinal bleeding in these patients are gastrointestinal angioectasias located within the small bowel that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The first and second-year survival benefits for advanced CHF patients on LVADs were demonstrated in the landmark REMATCH trial but also a 42 % incidence of gastrointestinal bleeding at 6 months of follow-up 9 . Other studies have reported incidence rates between 20 % to 30 % 3 10 . As noted in our results, the most common source of bleeding is small-bowel angioectasias/AVMs 4 11 12 13 14 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The first and second-year survival benefits for advanced CHF patients on LVADs were demonstrated in the landmark REMATCH trial but also a 42 % incidence of gastrointestinal bleeding at 6 months of follow-up 9 . Other studies have reported incidence rates between 20 % to 30 % 3 10 . As noted in our results, the most common source of bleeding is small-bowel angioectasias/AVMs 4 11 12 13 14 .…”
Section: Discussionmentioning
confidence: 92%
“…But major AEs related to BAE have been previously reported, including pancreatitis, perforation, aspiration pneumonia, and death 23 24 . Others have reported no AEs associated with the procedure 5 6 10 . In our study, no major AEs were noted related to the enteroscopy procedure despite the majority of patients being classified as ASA class IV.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation